Onontio, le médiateur: la gestion des conflits amérindiens en Nouvelle-France, 1603-1717 - Gohier, Maxime (Université du Québec à Montréal, 2004)
Keywords: Autochtones; Français

Onontio, le médiateur: la gestion des conflits amérindiens en Nouvelle-France, 1603-1717 - Gohier, Maxime (Septentrion, 2008)
Keywords: Autochtones; Français

Le corps amérindien dans les relations de voyage en Nouvelle-France au XVIIIe siècle - Chaffray, Stéphanie (Université Laval et Université Paris IV-Sorbonne, 2006)
Keywords: Autochtones; Français

Les soldats français à Montréal au XVIIIe siècle: activités et intégration sociale des soldats vues à travers les sources judiciaires - Charland, Stéphanie (Université de Montréal, 2006)
Keywords: Armée; Français

Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

Vivre comme frères: Native-French Alliances in the St Lawrence Valley, 1535-1667 - Cook, Peter (Université McGill, 2008)
Keywords: Autochtones; Français

Les anciens captifs de Deerfield au Canada: parcours de vie et intégration - Machabée St-Georges, Annabelle (Université de Montréal, 2010)
Keywords: Autochtones; Captifs; Français

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Déjouer l’ennui au fort de Ville-Marie à Montréal - Pothier, Louise (Revue d'histoire de la Nouvelle-France, 2023)
Keywords: Archéologie; Forts

Les relations diplomatiques franco-autochtones à Montréal, 1701-1713 - Delbreil, Constance (Université de Montréal, 2019)
Keywords: Autochtones; Français; Grande Paix de Montréal

La Grande Paix de Montréal de 1701: les voies de la diplomatie franco-amérindienne - Havard, Gilles (Recherches amérindiennes au Québec, 1992)
Keywords: Autochtones; Français; Grande Paix de Montréal

Les lieux de la paix de 1701, et autres considérations sur les campements amérindiens à Montréal - Johnson, Laurence (Recherches amérindiennes au Québec, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

Les signatures amérindiennes: essai d’interprétation des traités de paix de Montréal de 1700 et de 1701 - Guillaud, Yann; Delâge, Denis; D'avignon, Mathieu (Recherches amérindiennes au Québec, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

The Great Peace: Chronicle of a Diplomatic Saga - Beaulieu, Alain; Viau, Roland (Libre Expression, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

The Great Peace of Montreal of 1701: French-Native Diplomacy in the Seventeenth Century - Havard, Gilles (McGill-Queen's University Press, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

Des poils pubiens aux perles, de la chair au corps: essai sur la Grande Paix de Montréal de 1701 - Delâge, Denys (Éros et tabou. Sexualité et genre chez les Amérindiens et les Inuit, 2014)
Keywords: Autochtones; Français; Grande Paix de Montréal

Les drapeaux militaires en Nouvelle-France - Chartrand, René (Material History Review / Revue d’histoire de la culture matérielle, 1995)
Keywords: Armée

La gouvernance militaire en Nouvelle-France - Chartrand, René (Bulletin d'histoire politique, 2009)
Keywords: Armée

Le rappel de Maisonneuve en France - Lapierre, Michel; Gagnon, Louis (Montréal en tête, 2012)
Keywords: Chomedey de Maisonneuve, Paul (Maisonneuve, Paul de Chomedey de); Communautés religieuses; Gouverneurs; Société de Notre-Dame de Montréal; Sulpiciens

Lemoyne d'Iberville: A Soldier of New France - Crouse, Nellis Maynard (The Ryerson Press/Cornell University Press, 1954)
Keywords: Le Moyne d'Iberville et d'Ardillières, Pierre

La gouvernance judiciaire et militaire sous le Régime français - Robichaud, Léon (La gouvernance montréalaise : de la ville-frontière à la métropole, 2014)

La criminalité soldatesque au Canada sous le Régime français - Ste-Marie, Philippe (Université de Montréal, 2019)
Keywords: Criminalité

De la Grande Paix de 1701 à la Grande Guerre de Montréal de 1990 - Trudel, Pierre (Bulletin d'histoire politique, 2002)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre

After Ryswick: The Five Nations Iroquois in French Diplomacy - Miquelon, Dave B. (Native Studies Review, 2009)
Keywords: Autochtones; Français; Grande Paix de Montréal; Iroquois

La Grande Paix: chronique d'une saga diplomatique - Beaulieu, Alain; Viau, Roland (Libre Expression et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Iroquois

Philippe de Rigaud de Vaudreuil, Governor of New France 1703-1725 - Zoltvany, Yves F (McClelland and Stewart, 1974)
Keywords: Gouverneurs; Rigaud de Vaudreuil, Philippe de

De la Champagne à la Nouvelle-France, Claude de Ramesay (1659-1724) - Litalien, Raymonde (Catalogue de l'exposition Le Canada de Louis XIV, 1980)
Keywords: Gouverneurs; Ramezay, Claude de

Un défenseur de la Nouvelle-France, François Piquet, le "Canadien" (1708-1781) - Chagny, André (Librairie Emmanuel Vitte, 1913)
Keywords: Autochtones; Communautés religieuses; Missions; Piquet, François; Sulpiciens

Chant et mission en Nouvelle-France, espace et rencontre des cultures - Dubois, Paul-André (Université Laval, 2004)
Keywords: Autochtones; Chanson; Missions; Musique

Corvée Labour and the Habitant “Spirit of Mutiny” in New France, 1688-1731 - Tomczak, Richard H. (Labour / Le travail, 2021)
Keywords: Fortifications; Travail

Iberville et les historiens. Le parcours historiographique d'un héros de la Nouvelle-France - Camirand, David (Université de Montréal, 2007)
Keywords: Histoire; Historiens; Le Moyne d'Iberville et d'Ardillières, Pierre

"Cy devant soldat - après habitant": The Settling of the Carignan-Salières Regiment in New France - Gagné, Peter (Université Laval, 2005)
Keywords: Armée

Dollard Des Ormeaux and the Fight at Long Sault: Was Dollard the Saviour of New France? - Lanctot, Gustave (Canadian Historical Review, 1932)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

La redoute de Dollard à la Baie des Sauvages. Un fort défendu par dix-sept Français - Barbeau, Marius (Revue canadienne de géographie, 1959)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

The Surrender of Montreal to General Amherst de Francis Hayman et l'identité impériale britannique - Turcot, Laurent (Mens, 2011)
Keywords: Capitulation; Guerre; Peinture

Les officiers d'état-major des gouvernements de Québec, Montréal et Trois-Rivières sous le régime français - Roy, P.-G. (Revue canadienne, 1917)
Keywords: Armée

De la Nouvelle-Angleterre à la Nouvelle-France: l'histoire des captifs anglo-américains au Canada entre 1675 et 1760 - Fournier, Marcel (Société généalogique canadienne-française, 1992)
Keywords: Américains; Captifs

Montréal, 1701: Planting the Tree of Peace - Havard, Gilles (Signes des Amériques, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

Montréal, 1701: planter l'arbre de paix - Havard, Gilles (Signes des Amériques, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

2001: tricentenaire de la Grande Paix de Montréal - Beaudoin, Léo (Montréal en tête, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

L’implantation des soldats français de la guerre de Sept Ans au Canada (1755-1830) : espace, parcours de vie et intégration sociale - Cousineau, Hubert (Université de Sherbrooke, 2021)
Keywords: Famille; Guerre; Milice

Le tricentenaire de la Grande Paix de Montréal. Août 1701 - Beaudoin, Léo (Histoire Québec, 2001)
Keywords: Autochtones; Callière, Louis-Hector de; Français; Gouverneurs; Grande Paix de Montréal; Guerre; Iroquois

The Times and Trials of a Distinctive Colony: 1702-1760 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Alimentation; Artisans; Autochtones; Britanniques; Capitulation; Esclaves; Fortifications; Français; Grande Paix de Montréal; Marchands; Noirs; Seigneurie

''It was impossible to make any further resistance'': The Final Act Plays Out before Montreal - Cubbison, Douglas R. (All Canada in the hands of the British: General Jeffery Amherst and the 1760 campaign to conquer New France, 2014)
Keywords: Capitulation